Calcium carbonate sediment corrosion and formation investigation in drinking water distribution network in Sough City, Iran - Abdol Hosein Salehi Sarvak; Seyed Ali Almodaresi; Abolghasem Mirhosseini Deh-abadi; Masoud Reza Shishehbore; Abdol Hosein Kangazian; Ali Akbar Jamali (Scientific Reports)
Abstract One of the major problems facing the water industry is corrosion and sedimentation, which causes problems such as reduced water quality and the useful life of water supply network equipment. This study aimed to investigate the corrosion and sediments formed in the drinking water distribution network of Sough City. In this cross-sectional study, samples were prepared from 7 wells, water storage reservoirs, and a dedicated water supply network in this area from 2006 to 2017. The parameters included pH, TDS, water temperature, total alkalinity, calcium hardness, and total hardness indices of Langelier, Ryznar, Pokurious, and Aggressive were measured in all sources. The mean indices were -0.59 ± 0.62, 8.48 ± 0.79, 7.24 ± 0.28, and 12.01 ± 0.22, respectively. The average PSI in all seasons was more than 7, AI was equal to 12, and pH in all seasons was 7.8, but in the summer it increased slightly to 8.5. This research showed that the amount of corrosiveness and sedimentation of water is not related to physicochemical parameters. Examination of corrosion indices of the dedicated water supply network of Sough City in the summer of 2011 showed that the water of this network tends to calcium carbonate sedimentation. A magnetic field was used to remove sediments formed in this water distribution network.